Chemicals of Emerging Concern in Treated Wastewater Impact Microbial Growth - McLain, Nathan K.; Gachomo, Emma W. (Frontiers in Environmental Science, 2019)
Agriculture production in California is negatively impacted by soilborne fungi, such as Verticillium dahliae, and limited water availability for irrigation. Some regions have adapted the use of recycling wastewater, i.e., reclaimed water, to supplement the potable water supply. Wastewater purification is not fully efficient at removing all contaminants and small amounts of pharmaceutical products, known as chemicals of emerging concern (CECs), remain. Acetaminophen, trimethoprim, sulfamethoxazole and gemfibrozil are some of the most common CECs found in treated wastewater and were therefore used in this study. These CECs were evaluated for their potential to interact with microorganisms directly, or for their ability to alter the development of Verticillium wilt disease in eggplants. The microorganisms Verticillium dahliae, Fusarium oxysporum f. sp. lycopersici, Piriformospora indica, Phytopthora capsici, and Bradyrhizobium japonicum were used for in vitro growth assays in the presence of CECs. CECs induced varying responses in strains of the same fungi by promoting growth of one strain while inhibiting growth of the other. CECs influenced spore germination of V. dahliae and F. oxysporum. Greenhouse experiments in which Solanum melongena (eggplants) were inoculated with V. dahliae and irrigated with CECs were used to evaluate the impacts of these chemicals on disease development. Overall our results found that most of the organisms we tested were sensitive to the CECs. P. capsici was found to be the most sensitive microorganism, while B. japonicum growth was unaffected by the CECs at the concentrations used. The greenhouse assays results indicated that plant disease severity may be influenced by given CECs at certain stages of plant growth. Overall the results of this study indicate that the concentrations of CECs found in reclaimed water are occurring at biologically relevant concentrations.